PENGORGANISASIAN PEMAKAMAN DAN SKEMA KESEJAHTERAAN DALAM MASYARAKAT MUSLIM PERKOTAAN: STUDI KASUS DI KOTA YOGYAKARTA - Purno Aji, Subhan (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2018)
This paper treats the funeral organization as a welfare proxy (governance arrangement of market-state-society) in the context of a society that has undergone rationalization, secularization, medicalization, and loss of